Context-Dependent Cell Cycle Checkpoint Abrogation by a Novel Kinase Inhibitor - Massey, Andrew J.; Borgognoni, Jenifer; Bentley, Carol; Foloppe, Nicolas; Fiumana, Andrea; Walmsley, Lee (PLOS ONE, 2010)
Background Checkpoint kinase 1 and 2 (Chk1/Chk2), and the Aurora kinases play a critical role in the activation of the DNA damage response and mitotic spindle checkpoints. We have identified a novel inhibitor of these kinases and utilized this molecule to probe the functional interplay between these two checkpoints. Principal Findings Fragment screening, structure guided design, and kinase cross screening resulted in the identification of a novel, potent small molecule kinase inhibitor (VER-150548) of Chk1 and Chk2 kinases with IC50s of 35 and 34 nM as well as the Aurora A and Aurora B kinases with IC50s of 101 and 38 nM. The structural rationale for this kinase specificity could be clearly elucidated through the X-ray crystal structure. In human carcinoma cells, VER-150548 induced reduplication and the accumulation of cells with >4N DNA content, inhibited histone H3 phosphorylation and ultimately gave way to cell death after 120 hour exposure; a phenotype consistent with cellular Aurora inhibition. In the presence of DNA damage induced by cytotoxic chemotherapeutic drugs, VER-150548 abrogated DNA damage induced cell cycle checkpoints. Abrogation of these checkpoints correlated with increased DNA damage and rapid cell death in p53 defective HT29 cells. In the presence of DNA damage, reduplication could not be observed. These observations are consistent with the Chk1 and Chk2 inhibitory activity of this molecule. Conclusions In the presence of DNA damage, we suggest that VER-150548 abrogates the DNA damage induced checkpoints forcing cells to undergo a lethal mitosis. The timing of this premature cell death induced by Chk1 inhibition negates Aurora inhibition thereby preventing re-entry into the cell cycle and subsequent DNA reduplication. This novel kinase inhibitor therefore serves as a useful chemical probe to further understand the temporal relationship between cell cycle checkpoint pathways, chemotherapeutic agent induced DNA damage and cell death.